Special training modules to improve training system efficiency in boxing - Kiselev, V. A.; Cheremisinov, V. N.; Gorbachev, S. S.; Raschetin, G. A. (Theory and Practice of Physical Culture, 2019)
It is rather normal for the sport trainings that the sport excellence stage trainings tend to be less and less effective in the competitive progress domain. The study analyzes benefits of the special training modules to improve efficiency of the training system in elite boxing, with every successive module focused on specific physical qualities beneficial for progress. The article gives a sample elite boxer training module with analysis of the module design, its elements (micro-cycles) and relevant training methods and tools. Each training module shall ideally include the aerobic, glycolytic and alactate anaerobic mechanisms prioritizing elements in the following sequence: aerobic, glycolytic and alactate anaerobic. A special attention in the study was given to the technical and tactical training elements of the modular training model, with the trainings dominated by the boxing-specific exercises to secure progress in the specific motor skills and energy supply mechanisms in the regular boxing techniques and tactics excellence process.